Evaluation of myocardial injury from use of aortic cross-clamp and cardiopulmonary bypass duration in patients undergoing tetralogy of Fallot corrective surgery - Wardoyo, Suprayitno; Djer, Mulyadi M.; Busro, Pribadi Wiranda (Indonesian Pediatric Society, 2025)
Background Much remains unknown about the myocardial injury caused by aortic cross-clamp and cardiopulmonary bypass durations in children undergoing open-heart surgery, especially children with cyanotic congenital heart disease. To assess this injury, specific biomarkers can provide valuable insights. Troponin I (TnI) is known to be a specific marker of heart damage, while serum lactate serves as an indicator of tissue hypoperfusion and ischemic events. Additionally, malondialdehyde (MDA) is recognized as a marker of oxidative stress resulting from CPB machine usage. Objective To investigate the association of aortic cross clamp and CPB durations on myocardial injury and oxidative stress in children undergoing TOF corrective surgery. Methods We conducted this prospective study which included 29 patients diagnosed with TOF and who underwent corrective surgery. Troponin I and MDA levels were measured before surgery, 1 hour after surgery, and 8 hours after surgery. Lactate levels were measured in arterial blood specimens taken before surgery, as well as 1 hour, 6 hours, 12 hours, and 24 hours after surgery. Results Twenty-nine patients were included in this study and divided into groups based on aortic cross-clamp duration: shorter (<38 minutes) or longer (≥38 minutes), as well as based on CPB duration: shorter (<75 minutes) or longer (≥75 minutes), according to the median. Wilcoxon test indicated For the <38 min clamp duration group, there was only a significant increase in TnI at 1 hour compared to pre-op (P=0.048). However, there were no significant different in TnI, MDA, or lactate levels at any time point between the two CPB or cross-clamp groups.